Prophylaxis in hereditary angioedema (HAE) with C1 inhibitor deficiency. (March 2016) - Greve, Jens; Strassen, Ulrich; Gorczyza, Marina; Dominas, Nina; Frahm, Uta‐Marie; Mühlberg, Heike; Wiednig, Michaela; Zampeli, Vasiliki; Magerl, Markus
Summary: Hereditary angioedema (HAE) is a rare congenital disorder characterized by recurrent episodes of subcutaneous or submucosal edema. Laryngeal manifestations can be life‐threatening. In the majority of cases, the disease can be adequately treated with an on‐demand approach – in some cases, however, short‐ or long‐term prophylaxis is indicated. Attenuated androgens used to be the drugs of choice, but they are associated with considerable side effects and no longer commercially available in the German‐speaking countries of the EU. They are currently being replaced by more effective and more tolerable agents such C1‐inhibitors, the kallikrein inhibitor ecallantide, and the B2 receptor antagonist icatibant, which have recently obtained market authorization. These new drugs have had a major impact, especially on the indications and procedures for long‐term prophylaxis. According to the most recent international consensus papers and our own experience, self‐administered C1‐inhibitors are now the first option for long‐term prophylactic therapy. The decision for prophylaxis should no longer be based on single parameters such as the frequency of attacks but on adequate overall disease control including quality of life. More drugs are currently being developed, which may lead to further changes in the treatment algorithms of HAE.